Upaya Preventif Kekerasan Seksual pada Generasi Z melalui Kampanye Kesadaran oleh Komunitas Socialyouth - Annisya Zahra Lindra; Irhamni Rahman (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Sexual violence is a social issue that is developing dynamically, even across generations, with a real impact on generation Z. This generation experiences various forms of sexual violence, both in the environment, in public and in the online world. This research aims to describe the phenomenon of sexual violence among generation Z, as well as analyze preventive efforts carried out by the SocialYouth Community. This research uses a qualitative method with a case study type, where the SocialYouth community is the case study subject in this research. In seeking to prevent sexual violence in generation Z, SocialYouth uses awareness campaigns as the main strategy to prevent sexual violence, with online and offline approaches to reach generation Z who are closely connected to technology and social media. This campaign aims not only to disseminate information and show solidarity with victims, but also to encourage active participation from the community to be more aware of various issues of sexual violence.